Ube3a-ATS is an atypical RNA polymerase II transcript that represses the paternal expression of Ube3a - Meng, Linyan; Person, Richard E.; Beaudet, Arthur L. (Human molecular genetics, 2012)
The Angelman syndrome gene, UBE3A, is subject to genomic imprinting controlled by mechanisms that are only partially understood. Its antisense transcript, UBE3A-ATS, is also imprinted and hypothesized to suppress UBE3A in cis. In this research, we showed that the mouse antisense ortholog, Ube3a-ATS, was transcribed by RNA polymerase (RNAP) II. However, unlike typical protein-coding transcripts, Ube3a-ATS was not poly-adenylated and was localized exclusively in the nucleus. It was relatively unstable with a half-life of 4 h, shorter than most protein-coding RNAs tested. To understand the role of Ube3a-ATS in vivo, a mouse model with a 0.9-kb genomic deletion over the paternal Snrpn major promoter was studied. The mice showed partial activation of paternal Ube3a, with decreased expression of Ube3a-ATS but not any imprinting defects in the Prader-Willi syndrome/Angelman syndrome region. A novel cell culture model was also generated with a transcriptional termination cassette inserted downstream of Ube3a on the paternal chromosome to reduce Ube3a-ATS transcription. In neuronally differentiated embryonic stem (ES) cells, paternal Ube3a was found to be expressed at a high level, comparable with that of the maternal allele. To further characterize the antisense RNA, a strand-specific microarray was performed. Ube3a-ATS was detectable across the entire locus of Ube3a and extended beyond the transcriptional start site of Ube3a. In summary, we conclude that Ube3a-ATS is an atypical RNAPII transcript that represses Ube3a on the paternal chromosome. These results suggest that the repression of human UBE3A-ATS may activate the expression of UBE3A from the paternal chromosome, providing a potential therapeutic strategy for patients with Angelman syndrome.